L-arginine alleviates doxorubicin-induced endothelium-dependent dysfunction by promoting nitric oxide generation and inhibiting apoptosis. (1st July 2019) - Li, Xunan; Gu, Jie; Zhang, Yunlong; Feng, Siting; Huang, Xin; Jiang, Yinong; Xia, Yunlong; Liu, Yang; Yang, Xiaolei
Abstract: Background/aims: Patients with doxorubicin (Dox) treatment have a high risk of developing vascular toxicity with an unknown mechanism.l -arginine is a substrate for nitric oxide (NO). The decreased level of arginine-NO metabolite in Dox-treated cancer patients was associated with increased level of vascular damage, which promoted us to investigate the mechanism of Dox-induced vascular dysfunction and verify whetherl -arginine supplement could alleviate this vasculotoxic effect. Method: Within a mouse model of Dox injection (5 mg/kg i.p., 2 or 4 weeks), we measured vascular relaxation, blood pressure, vascular NO generation, apoptosis, and oxidative stress. We tested the efficacy ofl -arginine (1.5 mg/g/day, 4 weeks) on Dox-induced vascular relaxation, blood pressure, vascular NO generation, apoptosis, as well as oxidative stress. Results: Dox induced endothelium-dependent vascular dysfunction, which was associated with increased reactive oxidative stress (ROS) production and reduced NO generation in the vessel. ROS was required for Dox-induced apoptosis of both smooth muscle cells and endothelial cells. Dox treatment in mice increased blood pressure, but had no effect on vascular inflammation and fibrosis. L-aringine restored Dox-induced vascular dysfunction via enhancing vascular NO production and alleviating ROS-mediated apoptosis. Conclusion: We for the first time demonstratedl -arginine was effectively in suppressing Dox-induced vascular dysfunction, by attenuating vascular NO release and apoptosis. Our results provide a therapeutic target or a circulating marker for assessing vascular dysfunction which response to Dox treatment, and advance our understanding of the mechanisms of Dox-induced vascular dysfunction.